ALOKASI KREDIT PROGRAM KEMITRAAN PELAKU USAHA KULINER MITRA BINAAN PT TELEKOMUNIKASI INDONESIA TBK WILAYAH MANADO - Halomoan Lumban Toruan; Grace Adonia Josefina Rumagit; Leonardus Ricky Rengkung (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the allocation of credit funds in the Partnership Program by culinary business partners of PT Telekomunikasi Indonesia Tbk, Manado Region (Program Kemitraan oleh pelaku usaha kuliner Mitra Binaan PT Telekomunikasi Indonesia Tbk Wilayah Manado). Respondents were selected on all Culinary Business Partners. The data used in this study are primary data and secondary data. Primary data was obtained through direct interviews with 14 Foster Partners (respondent) using a questionnaire. Secondary data was obtained from the office of PT Telekomunikasi Indonesia Tbk in the Manado Region, the internet through the google scholar to get electronic books, journal articles and thesis related to the research topic about the allocation of the Partnership Program Credit. The analytical tool used in this research is descriptive statistical method. The results showed thatthe Partnership Credit Program was not used for productive purpose or sector, namely the consumptive sector but was used for household consumption, the cost of children's education, home renovation, buyingtelevision and saving. The percentage of the Partnership Program Credit used for the productive sector was 42.18%, the consumptive sector amounted to 27.75% and savings amounted to 30.07% from the totalamount of loans disbursed to the amount of Rp. 369,000,000, - for a total of 14 culinary business partners.*eprm*